OC-045 Faecal microbiota transplantation: implementing a new treatment for recurrent/refractory clostridium difficile infection using banked stool in a tertiary uk centre. (22nd June 2015) - Patel, KV; Digby-Bell, JL; Goel, RM; Henry, N; Sanderson, JD; Irving, PM; Goldenberg, S
Abstract : Introduction: Faecal microbiota transplantation is an effective treatment for recurrent/refractory Clostridium difficile infection (CDI). A randomised controlled trial reported sustained response in greater than 90% of patients, with an excellent safety profile. NICE approved the treatment as of March 2014. We introduced this new service in January 2015, setting up a stool bank to treat patients with recurrent CDI. We describe the process of initiating this service. Method: Stool donors are recruited from non-clinical members of hospital staff or patient selected donors. Donors must be healthy with a BMI <30, not taking oral medication, not received antibiotics in the previous 3 months and not be infected or at risk of any blood-borne viruses or transmissible infectious diseases. Donors are screened for diseases including Hepatitis A, B, C, E, HIV, HTLV, syphilis, CMV, EBV, Entamoeba histolytica, Strongyloides sterocaralis, Cryptosporidium, Giardia, C.difficile, H. Pylori, Norovirus, Campylobacter, Salmonella, Shigella, E.coli O:157, MRSA and multi-drug resistant coliforms. All transplant material has a batch number allowing full traceability. After screening, donors can provide stool for transplant for up to 3 months. >50 g of fresh donated stool is diluted with 250 mls 0.9% normal saline and 12.5% glycerol, filtered to remove large particles and immediately frozen at –80 0 C. Frozen stool can be stored for up to 6 months, offers the benefit of being available on demand, and is as effective as freshly used stool. Recipients are informed of the risks of colonoscopy and the risk of acquiring an unrecognised transmissible disease. Standard bowel preparation is given and the transplant is delivered through the endoscope channel with 75% of the donor stool placed in the caecum, and the remainder in the right colon. Alternatively, infusion can be performed via a nasoduodenal tube. Results: This pathway has been successfully implemented. Procedures are performed at the end of a list to allow subsequent deep cleaning of the endoscopy room, and donor stool is available in an ice box 30 min prior to procedure. Individuals are discharged home the day after the procedure, and contacted a week later to ascertain improvement in symptoms, and at 3-months for a second assessment including laboratory testing for C. difficile . Preliminary experience is promising with 100% of patients achieving clinical remission within a week of a single procedure. Conclusion: Introduction of a faecal transplant service for CDI is feasible. As with all new treatments safety is paramount. Thorough screening of donors, traceability of transplants and long term follow up is essential. Disclosure of interest: None Declared.